Mediation analysis of depressive symptoms in the relationship between pulmonary function (measured by peak expiratory flow) and cognitive function among older adults in Chinese - Chui-Yu Li; Hui-Rong Hu; Xiao-Qi Zhang; Yu-Mei Lin; Zhi-Yuan Chen (PLoS ONE, 2025)
Background Population aging has led to accelerated decline in pulmonary function, rising prevalence of depressive symptoms, and cognitive impairment, posing significant public health challenges. Although epidemiological evidence links poorer pulmonary function to subsequent cognitive decline, the pathways driving this relationship are not fully understood. We therefore investigated whether depressive symptoms mediate this relationship in older Chinese adults. Methods Data were drawn from the China Health and Retirement Longitudinal Study (CHARLS), including 2,320 participants aged 60 years and older. Pulmonary function was measured using peak expiratory flow (PEF). Depressive symptoms were assessed with the 10-item Center for Epidemiologic Studies Depression Scale (CES-D-10). Cognitive function was evaluated through tests of episodic memory and mental intactness. Mediation analysis was conducted using Baron and Kenny’s framework, and bootstrap analysis with 1,000 resamples was performed to assess direct and indirect effects. Sensitivity analyses ensured result robustness. Results Spearman correlation analysis showed that PEF was positively correlated with cognitive function (r = 0.20, P < 0.001) and negatively correlated with depressive symptoms (r = −0.15, P < 0.001). After adjusting for confounders, multivariate linear regression analysis indicated that baseline PEF was positively associated with subsequent cognitive function (β = 0.131, P < 0.001) and negatively associated with depressive symptoms (β = −0.064, P < 0.001). The mediation effect of depressive symptoms accounted for 9.1% of the total effect regarding baseline pulmonary function on cognitive function. Conclusion Depressive symptoms partially mediate the relationship between pulmonary function and cognitive function in older adults. These findings emphasize the need for mental health interventions to mitigate cognitive decline linked to reduced pulmonary function.